The role of probiotics in immunity formation - T. A. Ruzhentsova (Лечащий Врач)
The article presents the basic information about the various effects of probiotic strains on the formation of resistance of the human body to various pathogens and immune response. The data of studies confirming the influence of lacto- and bifidobacteria on the incidence of various acute respiratory and intestinal infections are presented. It is shown that preventive administration of compositions containing studied probiotics, or, if necessary, polycomponentsynbiotic complexes, promotes adequate functioning of the immune system, reduces seasonal morbidity in children and adults.